Molecular Characteristics of Vibrio Cholerae 01 from Miri, Sarawak - Vincent, Micky (2002)
The purpose of this case study was to evaluate the molecular characteristics of Vibrio cholerae 01 isolated during the biggest cholerae outbreak in Miri between November 1997 to April 1998. A total of 33 strains were examined. The randomly selected strains from over 1,000 fecal samples were studied for their antibiotic resistance, the occurrence of plasmids, RAPD-peR fingerprinting and the presence of the Ace, Ctxa, Ctxb and Zot genes. This study has shown that all strains were found to be resistant to four or more of the nineteen antibiotics and antimicrobial agents tested with MAR indices ranging between 0.21 to 0.74. These high MAR indexes suggest that all the strains originated from high-risk sources. The isolates exhibited high resistance to bacitracin (96.97%), cefuroxim (96.97%), cephalotin (90.91%), streptomycin (87.88%), rifampin (75.76%) and tetracycline (72.73%). The isolates in this study also demonstrated various degrees of resistance toward other antimicrobial agents used such as, carbenicillin (69.70%), amikacin (57.58%), ampicillin (54.54%), erythromycin (51.52%), nalidixic acid (51.52%), kanamycin (48.48%), oxacillin (33.33%), penicillin G (27.27%), ceftriaxone (21.21%), gentamycin (21.21%), vancomycin (21.21%) and cefoperazone (3.03%). All strains were, however, susceptible to chloramphenicol. According to the plasmid profile analysis, only one plasmid pattern was observed among the plasmids harboring isolates with the plasmid DNA bands ranging in sizes from 1.3 to 1.6 megadalton. Randomly amplified polymorphic DNA (RAPD) analysis was used.to analyze the genetic differentiation and relatedness of the 33 Vibrio cholerae 01 strains, using two arbitrary primers (GEN15003 and GEN15005), after screening a set of 10 primers. The two primers generated polymorphism in all 33 strains, producing typeable and reproducible results. The RAPD profiles revealed a wide variability and high level of DNA sequence diversity within the Vibrio cholerae 01 strains tested. This revealed no correlation with the source of isolation. The results from the RAPD-PCR fingerprinting were used to construct a dendrogram. From the dendrogram generated, three main clusters were observed and further subdivided into several subc1usters defining the genetic heterogeneity among the isolates. The detection of the specific genes by PCR yielded the following results; 32 of 33 (96.97%) isolates were positive for the Ace, C txa, Ctxb and Zot genes. Only 1 (3.03%) of the isolates exhibited the absences of the respective genes. The observations from all the investigations done on the isolates may indicate that multiple pathogenic strains of Vibrio cholerae 01, rather than a single type of infective strain cause these infections during the Miri cholera outbreak of 1997 and 1998.